A Proposal for Expanding Endarkened Transnational Feminist Praxis: Creating a Database of Women's Scholarship and Activism to Promote Health in Zimbabwe. (February 2017) - Zerai, Assata; Perez, Joanna; Wang, Chenyi
Western researchers often do not incorporate the voices of African women in their research endeavors; and a serious engagement in women's health activism in Zimbabwe cannot happen without this preliminary step. Endarkened feminist epistemologies have theorized a social science that refuses to sidestep African women's perspectives. As a corrective to conceptual quarantining of Black (African and African diasporic) feminist thought, the exciting body of literature in the field broadly characterized as Africana feminism has helped to legitimate the languages, discourses, challenges, unique perspectives, divergent experiences, and intersecting oppressions and privileges of African women's and girls' lives. In this article, we develop an emerging Africana feminist methodology to propose building a scholarship and activism database as well as guide an exploratory discussion of health activism in Zimbabwe.